Question

Solve by substitution.y = -2x + 1y = -6x - 11

Systems of equations
ANSWERED
asked 2021-02-09

Solve by substitution.
\(y = -2x + 1\)
\(y = -6x - 11\)

Expert Answers (2)

2021-02-10

Let: Solve by substitution.
\(y = -2x + 1\)
\(y = -6x - 11\)
Substitute (1) to (2) and solve for x: \(-2x+1=-6x-11\)
Add 6x to both sides: \(4x+1=-11\)
Subtract 1 from both sides: \(4x=-12\)
Divide both sides by 4: \(x=-3\)
Sovle for y using (1): \(y=-2(-3)+1\)
\(y=6+1\)
\(y=7\)
So, the solution of the system is: (-3,7)

19
 
Best answer
2021-08-10

My video will help you

9

expert advice

Have a similar question?
We can deal with it in 3 hours
...